PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Putri Maharani; I Nyoman Wijana Asmara Putra (ADMIN: Jurnal Administrasi Negara, 2025)
The objective of this research is to examine the relationship between understanding tax regulations, tax socialization, tax sanctions, and individual taxpayer compliance at KPP Pratama Badung Utara. Indonesia as a developing country is highly dependent on state revenue, especially in tax revenue. The aforementioned symptom in Indonesia today is the low compliance ratio of taxpayers in submitting tax returns due to the deficient tax system in Indonesia, namely the self-assessment system. Primary data, consisting of questionnaires, and secondary data from KPP Pratama Badung Utara were utilized in this study. The population in this study were 118,750 taxpayers, with a sample of 100 respondents determined using the Slovin formula with the accidental sampling method. Multiple linear regression analysis was the method of analysis. Results demonstrated that comprehension of tax regulations, tax socialization efforts, and tax sanctions positively influenced individual taxpayer compliance. The combined effect of these independent variables explained 53.6% of the variation in individual taxpayer compliance. This study suggests that KPP Pratama Badung Utara should focus on understanding of tax regulations, tax socialization, and tax sanctions to increase individual taxpayer compliance.